Compositional dependence of phase formation and mechanical properties in three CoCrFeNi-(Mn/Al/Cu) high entropy alloys. (December 2016) - Zhu, Z.G.; Ma, K.H.; Wang, Q.; Shek, C.H.
Abstract: Starting from three typical equiatomic CoCrFeNiMn, CoCrFeNiAl and CoCrFeNiCu high entropy alloys (HEAs), we systematically investigated the compositional dependence of phase formation and mechanical properties of 78 alloys by varying the atomic ratio of the constituent elements. It was found that the simple phase structures, including a single face-centered cubic (FCC) or body-centered cubic (BCC) phase, duplex FCC phases, duplex BCC phases, instead of intermetallics, could form within a broad compositional landscape in 68 out of the 78 alloys not limited to the equiatomic composition where the configurational mixing entropy is maximum. This fact indicates that it may be the nature of the constituent elements that leads to simple phase structure formation. With compositional variation, the microstructure and mechanical properties including hardness and tensile properties show corresponding changes. It was found that the hardness variation of samples within the same structure is smaller for the FCC than that of the BCC. Tensile results indicated that the tensile elongation of (CoCrFeMn)(100− x ) Ni x ( x = 0, 10 and 20) alloys increases with Ni addition due to the decreasing volume fraction of sigma phase. For the (CoCrFeAl)(100− x ) Ni x ( x = 27.3, 33.3, 38.5, 42.9 and 50) alloys, the yield strength decreases and tensile elongation increases with Ni addition due to decreasing volume fraction of BCC phase which is hard yet brittle. The present results are important to understand the phase formation and relationship between microstructure and mechanical properties in HEAs. Highlights: The phase formation of 78 alloys based on three typical CoCrFeNi-(Mn/Al/Cu) high entropy alloys was investigated. Simple phase structures could form in a very broad compositional landscape, not limited to the equiatomic composition. The current proposed phase formation parameters of HEAs were verified. The hardness variation of alloys with the same structure is smaller for FCC compared with that of the BCC structure.